Antioxidant Activity of Blackthorn (Prunus spinosa L.) Fruit Extract and Cytotoxic Effects on Various Cancer Cell Lines - Karakas, Nihal (Medeni Med J, 2019)
OBJECTIVE: Blackthorn (Prunus spinosa L. (Rosaceae) is a shrup whose fruits are consumed as food in Turkey. This study was aimed to evaluate antioxidant activity of methanol extract of P. spinosa and its cytotoxic effects on cancer cell lines. METHOD: Methanol extract of P. spinosa fruit was evaluated for its in vitro cytotoxic activity on multiform (GBM) brain cancer (LN229, U87 and T98G) and pancreas cancer (PANC-1 and AsPC-1) cell lines. Cell viability assays were performed by calculating the percentage of viable cells using a luminescence system, and spectrophotometrically. measuring its antioxidant ABTS and DPPH radical scavenging activities. Differences were considered as statistically significant at p*<0.001 and p**<0.0005 according to unpaired student t-test. RESULTS: Methanol extract of P. spinosa fruit showed 2548±18 mg GAE/100 g correspon-ding to the total phenolic content, and moderate antioxidant activity (0.1896±0.1143 and 0.0729±0.0348) by ABTS and DPPH assays. CONCLUSION: To the best of our knowledge, after evaluating the results of brain and pancreas cancer cell lines, significant cytotoxic activities with 50-63% cell viability of GBM brain cancer cells were determined while no cytotoxicity was observed on pancreas cancer cell lines, PANC-1; and AsPC-1. The results of this study showed that the methanol extract of P. spinosa fruit has significant antioxidant capacity and leads to statistically significant decreased viability on glioblastoma brain cancer cells.